Molecular Mechanism of Stem Cell Differentiation into Adipocytes and Adipocyte Differentiation of Malignant Tumor. (12th August 2020) - Zhang, Kexin; Yang, Xudong; Zhao, Qi; Li, Zugui; Fu, Fangmei; Zhang, Hao; Zheng, Minying; Zhang, Shiwu
Abstract : Adipogenesis is the process through which preadipocytes differentiate into adipocytes. During this process, the preadipocytes cease to proliferate, begin to accumulate lipid droplets, and develop morphologic and biochemical characteristics of mature adipocytes. Mesenchymal stem cells (MSCs) are a type of adult stem cells known for their high plasticity and capacity to generate mesodermal and nonmesodermal tissues. Many mature cell types can be generated from MSCs, including adipocyte, osteocyte, and chondrocyte. The differentiation of stem cells into multiple mature phenotypes is at the basis for tissue regeneration and repair. Cancer stem cells (CSCs) play a very important role in tumor development and have the potential to differentiate into multiple cell lineages. Accumulating evidence has shown that cancer cells can be induced to differentiate into various benign cells, such as adipocytes, fibrocytes, osteoblast, by a variety of small molecular compounds, which may provide new strategies for cancer treatment. Recent studies have reported that tumor cells undergoing epithelial-to-mesenchymal transition can be induced to differentiate into adipocytes. In this review, molecular mechanisms, signal pathways, and the roles of various biological processes in adipose differentiation are summarized. Understanding the molecular mechanism of adipogenesis and adipose differentiation of cancer cells may contribute to cancer treatments that involve inducing differentiation into benign cells.